2015
DOI: 10.1007/s10532-015-9746-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microbial transport during aerobic bioaugmentation of an RDX-contaminated aquifer

Abstract: In situ bioaugmentation with aerobic hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX)-degrading bacteria is being considered for treatment of explosives-contaminated groundwater at Umatilla Chemical Depot, Oregon (UMCD). Two forced-gradient bacterial transport tests of site groundwater containing chloride or bromide tracer and either a mixed culture of Gordonia sp. KTR9 (xplA (+)Km(R)), Rhodococcus jostii RHA1 (pGKT2 transconjugant; xplA (+)Km(R)) and Pseudomonas fluorescens I-C (xenB (+)), or a single culture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Although many RDX bioremediation studies have focused on biostimulation with an organic donor, recent studies have turned to bioaugmentation as an alternative bioremediation method to address the wide variety of site characteristics and the low cleanup goals for RDX. Initial bioaugmentation studies involved addition of aerobic RDXdegrading microbes (Crocker et al, 2015;Fuller et al, 2015Fuller et al, , 2017Michalsen et al, 2016). Achieving and maintaining aerobic conditions may be difficult in many contaminant plumes, however, especially when an organic donor source also needs to be added to support aerobic degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Although many RDX bioremediation studies have focused on biostimulation with an organic donor, recent studies have turned to bioaugmentation as an alternative bioremediation method to address the wide variety of site characteristics and the low cleanup goals for RDX. Initial bioaugmentation studies involved addition of aerobic RDXdegrading microbes (Crocker et al, 2015;Fuller et al, 2015Fuller et al, , 2017Michalsen et al, 2016). Achieving and maintaining aerobic conditions may be difficult in many contaminant plumes, however, especially when an organic donor source also needs to be added to support aerobic degradation.…”
Section: Introductionmentioning
confidence: 99%
“…However, RDX can be utilized as a source of nitrogen under aerobic conditions when other nitrogen sources are limited (Binks et al 1995;Fuller et al 2010a). 4-nitro-2,4-diazabutanal (4-NDAB) and methylenedinitramine (MEDINA) are typically produced in aerobic biodegradation of RDX associated with the XplA⁄XplB enzymes (Fournier et al 2004;Fuller et al 2010a;Crocker et al 2015). Despite the potential for RDX biodegradation under aerobic conditions, several studies have reported that aerobic RDX degraders may not be widespread in soil and groundwater, resulting in little or no RDX degradation under aerobic conditions (Fuller et al 2010b;Crocker et al 2015;Fuller et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite encouraging initial results, both bacterial numbers of Gordonia sp. KTR9 and xplA levels declined over time (Crocker et al 2015;Michalsen et al 2016;Fuller et al 2017). Factors preventing the accumulation of sufficient numbers of xplAB-containing soil bacteria to remove RDX-contamination, preventing downstream contamination are unknown, but xplAB-engineered plant endophytic, and associated rhizospheric bacterial communities indigenous to a contaminated site would be predicted to successfully reestablish in that environment.…”
Section: Endophytic and Rhizospheric Communitiesmentioning
confidence: 99%